Wireless Indoor Antenna Design For Smart TV Application - H.Sulaiman, H; I Khan, Z; E. Abd Rashid, N; K. Mohd Salleh, M; A. Wahab, N (International Journal of Engineering and Technology, 2018)
This paper present a new indoor digital microstrip TV antenna suitable for wireless application. A Rectangular Microstrip Patch Antenna for lower UHF (ultra high frequency) incorporated with a single Slotted Complementary Split Ring Resonator (SCSRR) on the partial ground plane is designed having a frequency at 566 MHz with bandwidth of 357 MHz. A single SCSRR is used as a miniaturization technique to reduce the size of the microstrip antenna that can be applied in lower UHF especially in DTV (Digital TV) broadcasting frequencies in Malaysia. The antenna design was limited to a size of 20.1 cm x 21.2 cm using FR-4 substrate with thickness 1.6 mm with dielectric constant of 4.3. The performance of the designed antenna is measured in terms of return loss, VSWR, radiation pattern, HPBW and line impedance at four frequencies; 478 MHz, 566 MHz, 606MHz, and 742 MHz. The proposed antenna is fabricated and measured in verifying the design.Â Â